2015
DOI: 10.4236/ojrad.2015.54034
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Physicians’ Knowledge, Attitude and Practices of Radiation Safety at Suez Canal University Hospital, Egypt

Abstract: Doctors who request imaging must be well trained in deciding whether diagnostic imaging is indicated and have an accurate knowledge of the associated risks. Although radiological doses are low and the chance of late effect is minimal, it should be kept as low as reasonably achievable. This cannot be achieved without a proper knowledge and adherence to safe practices. This cross-sectional study investigates the level of physicians' knowledge about radiation safety and their attitude towards radiation protection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
21
7
2

Year Published

2017
2017
2025
2025

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 18 publications
11
21
7
2
Order By: Relevance
“…Regarding the effect of occupation on practice of radiation protection ( Table 5), Abdellah et al (2015) in their study on assessment of physicians' knowledge, attitude and practices of radiation safety at Suez Canal University Hospital found inadequate practice among physicians and they found only half of the physicians were using lead gloves which was contrary to our results.…”
Section: El-feky Et Al (2017) Reportedcontrasting
confidence: 99%
See 1 more Smart Citation
“…Regarding the effect of occupation on practice of radiation protection ( Table 5), Abdellah et al (2015) in their study on assessment of physicians' knowledge, attitude and practices of radiation safety at Suez Canal University Hospital found inadequate practice among physicians and they found only half of the physicians were using lead gloves which was contrary to our results.…”
Section: El-feky Et Al (2017) Reportedcontrasting
confidence: 99%
“…Other Egyptian studies reported inadequate use of safety measures and practices in most ionizing radiation facilities (Abdellah et al, 2015 andEl-Feky et al, 2017) This research was carried out because it was noted that the level of awareness of the dangerous exposure to high levels of radiation by some health care workers in radiology departments was not adequate. Some neglected the use of personal dosimeters and others did not receive them.…”
Section: Shieldingmentioning
confidence: 99%
“…The aim of the present work was to evaluate the knowledge and awareness of physicians about the hazards of radiological examinations on the health of workers and their patients in Saudi Arabia. Several studies estimate the knowledge and awareness of physicians about the hazards of radiological examinations in Asia, Africa and Europe (Abdellah, Attia, Fouad, & Abdel-Halim, 2015;Alhasan, 2016;Hamarsheh & Ahmead, 2012;Illian, 2011;Madrigano, Abrão, Puchnick, & Regacini, 2014;Sin et al, 2013;Sundaran, 2017;Zewdneh, Dellie, & Ayele, 2012). Some of these studies showed a lack of knowledge and awareness in radiation protection such as African physicians (Abdellah et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies estimate the knowledge and awareness of physicians about the hazards of radiological examinations in Asia, Africa and Europe (Abdellah, Attia, Fouad, & Abdel-Halim, 2015;Alhasan, 2016;Hamarsheh & Ahmead, 2012;Illian, 2011;Madrigano, Abrão, Puchnick, & Regacini, 2014;Sin et al, 2013;Sundaran, 2017;Zewdneh, Dellie, & Ayele, 2012). Some of these studies showed a lack of knowledge and awareness in radiation protection such as African physicians (Abdellah et al, 2015). In addition, this study will compare the different background knowledge for physicians from different countries, including Saudis working in Saudi Arabia.…”
Section: Introductionmentioning
confidence: 99%
“…Bu nedenle hedef kitle olarak ilköğretim öğretmenleri seçilmiştir. Radyasyonun etkilerine karşı yapılan duyarlılık, farkındalık, algı ve çeşitli bilgilendirme çalışmaları olmakla beraber (Miller, 1968;Eijkelhof, Klaassen ve Millar, 1990;Togay, 2002;Prabhat, Sudhakar, Kumar ve Ramaraju, 2011;Mavi, 2008;Prather, 2005;Bakaç, Kartal Taşoğlu ve Usta, 2012;Bakaç, Kartal Taşoğlu, Çınar ve Dönmez, 2012;Abdellah, Attia, Fouad ve Abdel-Halim, 2015) alan yazında bu konuda yeterli sayıda çalışma da bulunmamaktadır. Bu çalışma; İlkokul ve ortaokulda çalışan öğretmenlerin radyasyon kavramı hakkında bilgi düzeyleri ve radyasyona karşı tutumlarının mevcut durumlarını tespit etmeği amaçlamıştır.…”
Section: Introductionunclassified